2020
DOI: 10.3389/fmicb.2020.01647
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions of Airway Bacterial and Fungal Communities in Clinically Stable Asthma

Abstract: Dysbiotic airway microbiota play important roles in the inflammatory progression of asthma, and exploration of airway microbial interactions further elucidates asthma pathogenesis. However, little is known regarding the airway bacterial-fungal interactions in asthma patients. We conducted a cross-sectional survey of the sputum bacterial and fungal microbiota from 116 clinically stable asthma patients and 29 healthy controls using 16S rRNA gene and ITS1 sequencing. Compared with healthy individuals, asthma pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 71 publications
(100 reference statements)
5
21
0
Order By: Relevance
“…The Simpson (P = 0:035) index of the EA subjects was significantly lower compared that of NEA subjects (Figure 2 (a)), which was consistent with previous studies in the asthmatic subjects [10,25]. A comparable result had been observed in COPD subjects; the EC subjects showed lower Chao1 index (P = 0:036) and Simpson index (P = 0:031) than NEC subjects (Figure 2(c)).…”
Section: Fungal Microbiota the Overviews Of Sequencing Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The Simpson (P = 0:035) index of the EA subjects was significantly lower compared that of NEA subjects (Figure 2 (a)), which was consistent with previous studies in the asthmatic subjects [10,25]. A comparable result had been observed in COPD subjects; the EC subjects showed lower Chao1 index (P = 0:036) and Simpson index (P = 0:031) than NEC subjects (Figure 2(c)).…”
Section: Fungal Microbiota the Overviews Of Sequencing Resultssupporting
confidence: 89%
“…In this study, NEA subjects showed higher α-diversity of bacteria compared with EA subjects (Figure 4(a), Chao1 index, P = 0:002), which coincided with the results of recent studies [8,25]. Compared with EC subjects, the NEC subjects also had significantly increased Chao1 (Figure 4(c), P = 0:004) index.…”
Section: Bacterial Microbiotasupporting
confidence: 90%
See 1 more Smart Citation
“…Perhaps fungal presence induces changes in the lung micro-environmental conditions that subsequently drives this compositional shift among bacterial communities to compensate. For example, enrichment of Moraxella species in asthmatic airways was found to interact negatively with multiple bacterial communities but positively with fungal communities suggesting complex interactions between the bacterial and fungal communities that may contribute to asthma pathogenesis [ 32 ] That said, it is important to note that limited fungal genome database may also explain the identified similarity between adult and pediatric groups. For example, recent check (July, 2020) of the NCBI Genome database https://www.ncbi.nlm.nih.gov/genome/browse#!/eukaryotes/fungi shown 6570 complete fungal genomes compared with > 252,000 complete bacterial genomes.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of NTM antibiotic treatment on the microbiome Antibiotics are a major cause of microbiota changes because these drugs are designed to attenuate bacterial growth and subsequently cause death. In gut and pulmonary microbiome studies, early antibiotic exposure in childhood has been identified as a risk factor for the development of obesity [71], asthma [72] and diabetes [73]. In adulthood, chronic exposure to antibiotics correlates with microbiome shifts that result in susceptibility towards pathogen colonisation, impaired host responses and chronic microbial dysbiosis [74].…”
Section: The Respiratory Microbiome and The Landscape Of Microbial Playersmentioning
confidence: 99%